"Forcing Every Thought and Action into Responsibility": An Unpublished Curriculum Vitae from Dietrich Bonhoeffer's Fiancé Maria von Wedemeyer. Edited with an Introduction and Commentary by Jutta Koslowski. Issue 1 (April 2023) - Koslowski, Jutta
This is the first publication of the Curriculum Vitae of Maria von Wedemeyer, fiancé of the famous theologian Dietrich Bonhoeffer who has been executed by the Nazis just a few days before the end of World War II as a resistance fighter against Hitler. Maria wrote this CV in the year 1948 at the age of 23, when she applied for a scholarship at Bryn Mawr College near Philadelphia. In Germany, she had studied mathematics at the University of Göttingen, and she intended to pursue studies in physics and history in order to become a teacher. Here application was approved and she remained in the United States for good: She was twice married and divorced, raised two sons and embarked on a career in the emerging computer industry before she died on Boston at the age of 53 in with cancer. Whereas Dietrich Bonhoeffer's popularity is still growing more than 75 years after his death, little is known about his family background. This is especially true for the women among his relatives – despite of their crucial importance for the resistance movement. Maria von Wedemeyer kept silent about her relationship with Dietrich for the most part of her life, trying to leave behind the terrible strokes of fate which she had experienced as a young woman: Her beloved father and brother were killed as soldiers at the Eastern Front in Russia, her family's state in Brandenburg was destroyed by the Red Army and her fiancé was killed by the Gestapo. However, Maria relates how deeply she was shaped by the Christian faith of her parents and about the aspirations she has to educate a new generation for a better future.